1997
DOI: 10.1073/pnas.94.13.7030
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-associated molecules regulate the formation of layer-specific cortical circuits

Abstract: The columnar organization of the mammalian neocortex is based on radially oriented axon collaterals which precisely link cells from distinct cortical layers. During development, these interlaminar connections are specific from their initial outgrowth: collaterals form only in the target layers and there are no transient axonal collaterals in the nontarget layers. To examine whether positional cues within individual cortical layers regulate the laminar specificity of collateral formation, explants of cells dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 49 publications
1
26
0
Order By: Relevance
“…To date it has been shown that retinal axons preferentially form branches in appropriate layers of fixed tectal tissues (Yamagata and Sanes, 1995) or in the membrane fraction obtained from the corresponding tectal region (Roskies and O'Leary, 1994). Cortical neurons have also been shown to form branches preferentially on membrane obtained from particular layers (Castellani and Bolz, 1997). These findings are consistent with the present results for the thalamocortical projection.…”
Section: Laminar Specificity Of Branch Formation On Fixed Cortexsupporting
confidence: 82%
“…To date it has been shown that retinal axons preferentially form branches in appropriate layers of fixed tectal tissues (Yamagata and Sanes, 1995) or in the membrane fraction obtained from the corresponding tectal region (Roskies and O'Leary, 1994). Cortical neurons have also been shown to form branches preferentially on membrane obtained from particular layers (Castellani and Bolz, 1997). These findings are consistent with the present results for the thalamocortical projection.…”
Section: Laminar Specificity Of Branch Formation On Fixed Cortexsupporting
confidence: 82%
“…Finally, an increase in nonspecific connections might cause responses to preferred and nonpreferred stimuli to regress toward the mean response to all stimuli, decreasing peak, but not total, responsiveness. It has been argued that promiscuous sprouting would cause thalamocortical transneuronal label to spread beyond layer IV, which has not been seen, but in fact other chemical clues may constrain axons to the appropriate layer (Castellani and Bolz, 1997). These experiments with high concentrations do not directly address a role for endogenous NT-4/5.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies strongly suggest that molecular cues are used by developing pyramidal neurons to establish their initial layer-specific axonal arbors (Bolz and Castellani, 1997;Castellani and Bolz, 1997;Castellani et al, 1998;Dantzker and Callaway, 1998;Butler et al, 2001;Borrell and Callaway, 2002). A distinct neuronal class would respond differently to cues found within layer 4 and arborize within this layer where growth of axons from other layer 2/3 pyramidal neurons is excluded.…”
Section: Discussionmentioning
confidence: 99%